INTEREST RATE CHANGES AND FINANCIAL PERFORMANCES OF OIL FIRMS IN THE AFRICAN STOCK MARKET. (Journal of the Management Sciences, 2024)
Prices of oil and gas are generally known to be highly volatile and the recent price changes have caused several concerns for consumers, corporations and countries alike as they experience high dependency on oil and gas for transportation, electricity generation and industrial production. The specific objective of the study was to investigate interest rate change effect on financial performance of the oil and gas sector. The study also evaluated Firm size and firm age as a control variable. In so doing, data was sourced from active oil and gas firms quoted in the African Stock market. Panel data regression using Hausman’s fixed effect and random effect models was adopted. However, the study also conducted other diagnostic tests like multicollinearity test using Variance inflation factor, Heteroscedasticity test, correlation analysis. Findings showed that Interest rate changes has positive and no significant effect on the performance of oil and gas firms listed on African stock market. Firm size does not have significant effect on interest rate and financial performance of oil and gas firms on the African stock market.And recommend that, Oil and gas companies increase the price of their commodity in order to overcome the rise in interest rate, as such increase their profit. However, management can ignore interest rate fluctuations since it’s not significant in determining the profitability of their firms. And that Government should find a way of stabilizing interest rate using its monetary policies to cub the fluctuations in oil price
Keywords: Interest rate, financial performance, firms, stock market, Africa